(untitled) (American Journal of Technology and Applied Sciences, 2023)
Steam oil compression is the most common method of increasing the oil yield of formations, and it has many advantages over all other methods in the compression of high-viscosity oils. In this process, steam is pumped into low-temperature and high-viscosity oil layers from the surface of the earth, within the boundaries of the oil field, through special steam-driving wells. Steam at 2300 C is 3-3.5 times more than hot water, has a large heat capacity (more than 5000 kDj/kg), brings a lot of heat energy to the layer. This input heat energy is spent on heating the formation, reducing the relative permeability and oil viscosity, saturating the formation and expanding oil, water, and gases.